Potential Application of Plant-Based Functional Foods in the Development of Immune Boosters - Linlin Jiang; Guoqing Zhang; Guoqing Zhang; Ye Li; Guirong Shi; Minhui Li; Minhui Li; Minhui Li (Frontiers Media S.A., 2021)
Immune dysfunction, which is responsible for the development of human diseases including cancer, is caused by a variety of factors. Therefore, regulation of the factors influencing the immune response is a potentially effective strategy to counter diseases. Presently, several immune adjuvants are used in clinical practice to enhance the immune response and host defense ability; however, synthetic drugs can exert negative side effects. Thus, the search for natural products of plant origin as new leads for the development of potent and safe immune boosters is gaining considerable research interest. Plant-based functional foods have been shown to exert several immunomodulatory effects in humans; therefore, the application of new agents to enhance immunological and specific host defenses is a promising approach. In this comprehensive review, we have provided an up-to-date report on the use as well as the known and potential mechanisms of bioactive compounds obtained from plant-based functional foods as natural immune boosters. Plant-based bioactive compounds promote immunity through multiple mechanisms, including influencing the immune organs, cellular immunity, humoral immunity, nonspecific immunity, and immune-related signal transduction pathways. Enhancement of the immune response in a natural manner represents an excellent prospect for disease prevention and treatment and is worthy of further research and development using approaches of modern science and technology.